Different Intensity Exercise Preconditions Affect Cardiac Function of Exhausted Rats through Regulating TXNIP/TRX/NF-ĸBp65/NLRP3 Inflammatory Pathways. (9th June 2020) - Li, Yuemin; Xu, Peng; Wang, Yang; Zhang, Junshi; Yang, Mei; Chang, Yumei; Zheng, Ping; Huang, Heling; Cao, Xuebin
Abstract : Objective . To investigate whether exercise preconditioning (EP) improves the rat cardiac dysfunction induced by exhaustive exercise (EE) through regulating NOD-like receptor protein 3 (NLRP3) inflammatory pathways and to confirm which intensity of EP is better. Method . Ninety healthy male Sprague Dawley rats were randomly divided into five groups: a control group (CON), exhaustive exercise group (EE), low-, middle-, and high-intensity exercise precondition and exhaustive exercise group (LEP + EE, MEP + EE, HEP + EE group). We established the experimental model by referring to Bedford's motion load standard to complete the experiment. Then, the pathological changes of the myocardium were observed under a light microscope. Biomarker of myocardial injury in serum and oxidative stress factor in myocardial tissue were evaluated by ELISAs. The cardiac function parameters were detected using a Millar pressure and volume catheter. The levels of thioredoxin-interacting protein (TXNIP), thioredoxin protein (TRX), nuclear transcription factor kappa Bp65 (NF-ĸBp65 ), NLRP3, and cysteinaspartate specific proteinase 1 (Caspase-1) protein in rats' myocardium were detected by western blotting. Results . 1. The myocardial structures of three EP + EE groups were all improved compared with EE groups. 2. The levels of the creatine phosphating-enzyme MB (CK-MB), reactive oxygen species (ROS), interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor alpha (TNF- α ) in three EP + EE groups were all increased compared with CON but decreased compared with the EE group (P < 0.05 ). 3. Compared with the CON group, slope of end-systolic pressure volume relationship (ESPVR), ejection fraction (EF), and peak rate of the increase in pressure (d P /d t max ) all dropped to the lowest level in the EE group (P < 0.05 ), while the values of cardiac output (CO), stroke volume (SV), end-systolic volume (Ves), end-diastolic volume (Ved), and relaxation time constant (Tau) increased in the EE group (P < 0.05 ). 4. Compared with the CON group, the expression levels of TXNIP, NF-ĸBp65, NLRP3, and Caspase-1 all increased obviously in the other groups (P < 0.05 ); meanwhile, they were all decreased in three EP + EE groups compared with the EE group (P < 0.05 ). 5. NLRP3 was positively correlated with heart rate, IL-6, and ROS, but negatively correlated with EF (P < 0.01 ). Conclusion . EP protects the heart from EE-induced injury through downregulating TXNIP/TRX/NF-ĸBp65 /NLRP3 inflammatory signaling pathways. Moderate intensity EP has the best protective effect.